Negara, Pasar, dan Problem Pendalaman Demokrasi Pasca Orde Baru - Ade Marup Wirasenjaya (Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract: This paper tries to elaborate about deepening integration of state to neoliberal regime and its implication on deepening of democracy in domestic level. After the New Order era, the mass political identity all channeled through very limited political institutions proved to re-discover the primordial basis. Along with the growth of neo-liberal regime, changing also the constructt of the state formation by the international structures. Construction of the state as an agent of the capitalist is changing. If liberalism tend to create state as repressive apparatus, the neoliberal regime tried to construct a democratic state. Moreover, the neoliberal regime also began creating directly political identity that they expect in domestic level.Keywords: Neoliberalism, New Order Era, Deepening Democracy, Constructivist, Floating Mass